2016
DOI: 10.1007/s00345-016-1944-x
|View full text |Cite
|
Sign up to set email alerts
|

Proctors exploit three-dimensional ghost tools during clinical-like training scenarios: a preliminary study

Abstract: PurposeIn this study, we examine three-dimensional (3D) proctoring tools (i.e., semitransparent ghost tools overlaid on the surgeon’s field of view) on realistic surgical tasks. Additionally, we develop novel, quantitative measures of whether proctors exploit the additional capabilities offered by ghost tools.MethodsSeven proctor–trainee pairs completed realistic surgical tasks such as tissue dissection and suturing in a live porcine model using 3D ghost tools on the da Vinci Xi Surgical System. The usability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
25
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 18 publications
0
25
0
Order By: Relevance
“…Preliminary studies conducted by Jarc et al (using the ghost tool platform with da Vinci surgical system) demonstrated effectiveness for both trainees and proctors during robot-assisted dry-lab training exercises, 7 and robot-assisted tissue dissection and suturing tasks on a live porcine model. 8 In both industry [9][10][11][12][13][14][15][16][17][18][19] and academia, [6][7][8][20][21][22][23][24][25][26][27] tele-mentoring solutions have been developed. These solutions facilitate transfer of information from a specialist surgeon to the operating surgeon via a communication channel and enables tele-mentoring during different types of surgeries.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Preliminary studies conducted by Jarc et al (using the ghost tool platform with da Vinci surgical system) demonstrated effectiveness for both trainees and proctors during robot-assisted dry-lab training exercises, 7 and robot-assisted tissue dissection and suturing tasks on a live porcine model. 8 In both industry [9][10][11][12][13][14][15][16][17][18][19] and academia, [6][7][8][20][21][22][23][24][25][26][27] tele-mentoring solutions have been developed. These solutions facilitate transfer of information from a specialist surgeon to the operating surgeon via a communication channel and enables tele-mentoring during different types of surgeries.…”
mentioning
confidence: 99%
“…Augmented ghost tools have also been proposed for robotic surgery. 7,8 Though dynamic in nature, it renders only the tooltips without complete body of the surgical instrument. Apart from visualisation, this also limits the realism of augmented surgical tools' motion (as the constraints imposed by the incision points and the tools' kinematic are not taken into consideration).…”
mentioning
confidence: 99%
“…After removal of duplicates and screening of titles and abstracts, 157 full-text articles were assessed. A total of 66 studies were subsequently assessed as being suitable for inclusion 7-72 (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…More recent telecommunication technologies would certainly help to improve the perception of telementoring within this trial, particularly the advent of augmented and virtual reality. 31,71 All 4 studies reported no effect on postoperative or objective educational outcomes.…”
Section: Discussionmentioning
confidence: 99%
“… 53 54 Moreover, more recent telecommunication technologies would certainly help to improve the perception of telementoring, particularly the advent of augmented and virtual reality. 55 56 Again, there are no studies identified specific to gynaecology, however, based on the studies available from other specialties, it could well be piloted within gynaecology.…”
Section: Discussionmentioning
confidence: 99%